The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201705140
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Devices Prepared through a Trihydroxy Substitution Strategy on an Unsymmetrical Squaraine Dye

Abstract: A series of unsymmetrical arene-1,3-squaraine (USQ) derivatives with two, three, or four hydroxy (-OH) substituents, namely, USQ-2-OH, USQ-3-OH, or USQ-4-OH, respectively, were designed and synthesized, and the effect of the number of hydroxy groups on the optoelectronic properties of USQs were investigated. Despite the three compounds having similar UV/Vis absorption and HOMO energy levels, solution-processed bulk-heterojunction (BHJ) small-molecule organic solar cells with USQ-3-OH as electron-donor material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Binary and ternary BHJ cells were fabricated with USQ3OH and/or IDPSQ as the electron donor and PC 71 BM as the electron acceptor. On the basis of our previous results, the optimal D:A ratio of 1:3 was employed in this study. , A conventional device structure comprising ITO/MoO 3 (8 nm)/blend (∼80 nm)/LiF (0.8 nm)/Al (100 nm) was employed. The photovoltaic data for all devices are summarized in Tables and S2, and representative current density–voltage ( J – V ) and external quantum efficiency (EQE)–wavelength curves are shown in Figures , S1, and S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary and ternary BHJ cells were fabricated with USQ3OH and/or IDPSQ as the electron donor and PC 71 BM as the electron acceptor. On the basis of our previous results, the optimal D:A ratio of 1:3 was employed in this study. , A conventional device structure comprising ITO/MoO 3 (8 nm)/blend (∼80 nm)/LiF (0.8 nm)/Al (100 nm) was employed. The photovoltaic data for all devices are summarized in Tables and S2, and representative current density–voltage ( J – V ) and external quantum efficiency (EQE)–wavelength curves are shown in Figures , S1, and S2.…”
Section: Resultsmentioning
confidence: 99%
“…USQ3OH and IDPSQ were synthesized and purified according to published methods. Both squaraines can be easily prepared without any highly toxic reagents or complex reaction schemes, which are critical issues for ultimate manufacture.…”
Section: Methodsmentioning
confidence: 99%
“…recently synthesized SQ48–SQ50 with two, three or four hydroxy substituents, respectively. [ 68 ] They found that despite the number of OH groups had a negligible influence on the absorption and HOMO energy levels, the trihydroxy‐substituted SQ49‐based devices interestingly showed the best photovoltaic performance with a PCE of 6.07% and a J SC of 14.95 mA cm −2 . The detailed morphological study showed that the smaller phase separation for the SQ49/PC 71 BM blended film made a major contribution to enhanced device performance as shown in Figure 8c,d.…”
Section: Squaraine‐based Functional Materials For Photovoltaic Applicmentioning
confidence: 99%
“…A breakthrough was made in 2008; Marks et al developed a new type of hydrazine end‐capped SQs as the donor materials in the bulk heterojunction (BHJ) OSCs, and an encouraging PCE of 1.24% was produced. Subsequently, the photovoltaic performance of SQs has been gradually elevated with further development of new material exploitation and device engineering . Thus far, PCEs over 7% have been demonstrated in both single‐junction and tandem BHJ devices merely with SQs as the donors .…”
Section: Introductionmentioning
confidence: 99%